Jackie Robinson - Wheeler, Jill C., 1964- (Edina, Minn. : ABDO Pub., 2003)
A biography of the first African American to break the color barrier in major league baseball.
Includes index.
Keywords: Robinson, Jackie, -- 1919-1972 -- Juvenile literature; Robinson, Jackie, -- 1919-1972; Baseball players -- United States -- Biography -- Juvenile literature; African American baseball players -- Biography -- Juvenile literature; Baseball players; African Americans -- Biography